Peri-procedural Trans-esophageal Echocardiographic Sizing of the Native Left Ventricular Outflow Tract During Edwards INTUITY Valve Implantation - Lim, Kevin; Ho, Yan Kit; Chow, Simon Chi Ying; Fujikawa, Takuya; Lee, Alex Pui-Wai; Wong, Randolph Hung Leung (Frontiers in Cardiovascular Medicine, 2021)
1 Background The Edwards INTUITY rapid deployment valve was anchored on the left ventricular outflow tract (LVOT) by radial force akin to transcatheter balloon-expandable valves. This design feature facilitates minimally invasive and complex procedures but comes at the price of compressing the atrioventricular conduction bundle and potential requirement for pacemaker implantation. 2 Methods A retrospective observational study was conducted on 30 consecutive patients who received the INTUITY valve at our institution from August 2018 to January 2021. Demographical, clinical and echocardiographic parameters were collected for 90 days postoperatively. We performed retrospective virtual sizing of the native LVOT at the landing site of the sub-annular stent. A line was drawn from the inner edge of the septal endocardium to the inner edge of the anterior mitral leaflet in mid-systole, parallel to the aortic annulus, 6mm to 8mm apical to the aortic annulus depending on the valve size and the corresponding stent length. Risk factors associated with new onset conduction disturbances, defined as the occurrence of bundle branch block or complete heart block, were analyzed. 3 Results Operative mortality was 3.3%. 2 patients (5.9%) had moderate PVL by the third month of follow-up. 2 patients (6.7%) had pacemakers preoperatively and were excluded from the subsequent analysis. New onset conduction disturbances occurred in 4 of the remaining 28 patients (14.3%). This included two cases of persistent left bundle branch block and two cases of permanent pacemaker implantation due to complete heart block. Univariate analysis identified over-sizing of the native LVOT by 5mm or more as a significant risk factor associated with conduction disturbance. 4 Conclusion During INTUITY vale implantation, in addition to the aortic annulus, the landing site of the sub-annular stent within the native LVOT should also be sized pre-bypass. Over-sizing the native LVOT by 5mm or more is associated with an increased risk of new onset conduction disturbances and should be avoided.